Probabilistic-automaton modeling in soils migration processes research - Котовенко, Олена Андріївна; Мірошниченко, Олена Юріївна; Березницька, Юлія Олегівна; Шосталь, Юлія Володимирівна (Eastern-European Journal of Enterprise Technologies, 2014)
Structural-functional systems stochastic approach to the study and analysis of the process of migration accumulation of substances in the soil was presented in the paper. The purpose of the model investigation of the considered system is to study stochastic flow patterns of substances, which in some discrete time points come in the studied type of soil. The feasibility of the approach to solving a given problem is caused by dynamic process of migration accumulation of substances, as well as a large number of probabilistic factors of influence. The proposed approach is founded on the theory of probabilistic-automaton modeling of dynamic processes, which is based on the selected Moore automaton. The authors have synthesized probabilistic-automaton model of migration accumulation of certain substances in specific-type soil subsystems. The input parameters of this model are statistical data, relating to the time points of substances arrival in the soil and the amount of certain substances arrival at fixed, sufficiently large time intervals. Depending on the accumulation intensity of anthropogenic changes and conditional intensity of equilibrium transitions of ecosystem, expressions for the probability of system stable functioning take different forms. According to examples of using the synthesized model, this approach allows to conduct research, analysis and forecasting of processes of migration accumulation of pollutants under anthropogenic load and is one of the most suitable for environmental studies.